Testing the Grossman model of medical spending determinants with macroeconomic panel data - Jochen Hartwig; Jan-Egbert Sturm (Chemnitz University of Technology, Faculty of Economics and Business Administration, 2017)
Michael Grossman's human capital model of the demand for health has been argued to be one of the major achievements in theoretical health economics. Attempts to test this model empirically have been sparse, however, and with mixed results. These attempts so far relied on using – mostly cross-sectional – micro data from household surveys. For the first time in the literature we bring in macroeconomic panel data for 29 OECD countries over the period 1970-2010 to test the model. In order to check the robustness of the results for the determinants of medical spending identified by the model, we include additional covariates that have been suggested as determinants for medical spending in an Extreme Bounds Analysis (EBA) framework. The preferred model specifications (including the robust covariates) lend some support to the empirical relevance of the determinants of medical spending identified by the Grossman model, except for the relative medical price.
Keywords: C12; C23; I10; I12; 330; Medical spending; Grossman model; Extreme Bounds Analysis; OECD panel